A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

Collective action in comparative and empirical perspective: towards a socio-legal theory - Fortes, Pedro Rubim Borges (University of Oxford, 2016)
This DPhil thesis enhances existing understandings of collective action through a comparative and empirical study. Empirical analysis of economic, political, juridical, and social dimensions of the Brazilian experience reveals that some central understandings in existing literature are not borne out in this empirical context. In particular, the assertion that low monetary incentives for individuals hinder growth in use of collective action is strongly challenged. The Brazilian experience is contextualised through comparative analysis of three legal traditions of collective action: class actions; collective redress; and civil public actions. The Brazilian system presents a setting with potential for regulatory enforcement of consumer protection law, but rare episodes of consumer compensation or the imposition of punitive damages on corporations. With low monetary incentives, the growth of collective actions is explained by non-monetary incentives and investment in social capital through development of institutional trust and legal institutions. Collective actors develop their organisational infrastructure and perform their roles as representatives through institutional dynamics of concentration, competition, cooperation, and deference. The coexistence of multiple institutional actors in the regulatory space reduces agenda control, increases opportunities for consumer participation, and increases oversight of regulatory capture. The categories of diffuse, collective, and homogeneous individual rights explain the role of law in establishing procedural pathways and special features. This study is broadened through analysis of the legal environment and the potential regulatory impact of collective actions on the social relationships between businesses and consumers. I also evaluate limitations and possibilities regarding access to justice, judicial economy, compensation, and deterrence. This thesis indicates the possibility of developing a socio-legal theory of collective action, which would enhance our understanding of the complex dynamics at play by going beyond analysis of the consumer experience as merely an economic transaction or a legal object, analysing them instead as a complex social relationship.
Keywords: Collective action; Consumer (protection); Consumer compensation; Droit de la consommation

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
URI: https://repository.up.ac.za/handle/2263/56056
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation